LITERARY-MATHEMATICAL LIVING ROOM AS AN INNOVATIVE FORM OF ADDITIONAL EDUCATION OF YOUNGER ADOLESCENTS - Kondaurova, I.K; Fedorova, L.S (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
The General characteristic of additional education of younger teenagers is presented in the article. The definition of literary-mathematical living room as an innovative form of additional school education is clarified. Distinctive features that determine the uniqueness of the studied form: the inclusion in the content of the living room of literary and mathematical material; holding the living room in a cozy atmosphere, in an atmosphere of relaxation and trusting communication; the content of the living room and the composition of the participants are depended on the initiative and wishes of students. Requirements that must be met in the preparation and conduct of events in the literary and mathematical living room, are formulated. Methodological support of the literary and mathematical living room (including the work plan of the literary and mathematical living room; scenario of the evening «Arithmetic L. N. Tolstoy») is presented. The results can be used in educational institutions and organizations of additional education to improve the efficiency of the educational process.